Matra Basti in the Management of Katigraha (AYUSHDHARA, 2024)
Katigraha is one of the most common encountered diseases in present era. In this condition Shoola (pain) and Stabhdhata (stiffness) is seen in the Katipradesh (low back). In this condition Shuddha vata or Samavata gets lodged at Katipradesh and produces symptoms. Katigraha which is correlated with lumbar spondylosis, it is a degenerative condition that effects the disc, vertebral bodies and joints associated with lumbar spine. The current case study was carried out at the department of Panchakarma Shri Shivayogeeshwar Rural Ayurvedic Medical College, Hospital and Post Graduate Research Centre, Inchal. A 38 year old female patient with Katigraha was treated with the Samanya chikitsa of Vata vyadhi that is Abhyanga, Swedana, Basti, and Katibasti. Treatment was given for a period of 7 days. Patient got relief in pain and stiffness and also improvement in walking was seen. Clinically cardinal symptoms were significantly reduced. Radiologically spine showed improvement.